PENGEMBANGAN MEDIA KOTAK SIANG MALAM (KOSIMA) UNTUK MEMFASILITASI KEMAMPUAN KOGNITIF ANAK USIA 5-6 TAHUN - Martina, Alis; Mulyana, Edi Hendri; Rahman, Taopik (Universitas Pendidikan Indonesia (UPI), 2021)
This research is motivated by the problem of low cognitive abilities and limited learning media in the field, especially for delivering material day and night. The purpose of this research is to develop learning media to deliver material day and night according to the needs in the field. Based on the findings of the problem in the field, the researchers compiled and designed the Day and Night Box media to facilitate the cognitive abilities of children aged 5-6 years. The research method used is the development of the Educational Design Research (EDR) design by McKenney and Reeves. The EDR research procedure has 3 main stages, namely, the Analysis and Exploration stage; stage of Design and Construction (Design and Construction); and the Evaluation and Reflection stage. Based on the results of the analysis of product trial data, the Box Day and Night media to facilitate the cognitive abilities of children aged 5-6 years has been successfully developed and is suitable for use in learning in Early Childhood Education (PAUD).Penelitian ini dilatarbelakangi permasalahan mengenai rendahnya kemampuan kognitif dan terbatasnya media pembelajaran dilapangan khususnya untuk menyampaikan materi siang malam. Tujuan dilakukan penelitian ini untuk mengembangkan media pembelajaran untuk menyampaikan materi siang malam yang sesuai dengan kebutuhan dilapangan. Berdasarkan temuan masalah dilapangan peneliti menyusun dan merancang media Kotak Siang Malam untuk memfasilitasi kemampuan kognitif anak usia 5-6 tahun. Metode penelitian yang digunakan yaitu pengembangan dengan desain Educational Desain Research (EDR) karya McKenney dan Reeves. Prosedur penelitian EDR terdapat 3 tahap utama yaitu, tahap Analisis dan Eksplorasi (Analysis and Exploration); tahap Desain dan Konstruksi (Design and Construction); dan tahap Evaluasi dan Refleksi (Evaluation and Reflection). Berdasarkan hasil analisis dari data uji coba produk, media Kotak Siang Malam untuk memfasilitasi kemampuan kognitif anak usia 5-6 tahun ini telah berhasil dikembangkan dan layak digunakan dalam pembelajaran di Pendidikan Anak Usia Dini (PAUD).